(untitled) (MAUSAM, 2025)
In north-east India, the Corner Mountain is an almost right angled corner, which is made between the Khasi-Jayantia hills (KJH) & the Assam-Burma hills (ABH). In this paper, has been made to analysis the effects of orographic rainfall during the south west monsoon season (SWMS) over the north-east region of India, in a baroclinic mean flow. To construct this model a 3-D laminar, non-viscous, adiabatic, Boussinesq & non rotational moist airflow has been considered. The basic flow has two components, zonal wind U(z) and meridional wind V(z) and the Brunt-Väisälä frequency (N) is taken to be variant with height. The non-linear governing equations of the airflow are linearized by using the perturbation technique. To compute the rainfall intensity (RFI), the vertical velocity ( ) is obtained by quasi-numerical approach. In this study, two selective dates has been considered and all results have compared to the earlier researchers.